2003
DOI: 10.1046/j.1365-2141.2003.04715.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult T‐biphenotypic acute leukaemia: clinical and biological features and outcome

Abstract: Summary.  Biphenotypic acute leukaemia with T‐lymphoid and myeloid markers is rare and poorly documented. In the Leucemie Aigue Lymphoblastique de l'Adulte (LALA) prospective trial (LALA 94) of treatment for adult acute lymphoblastic leukaemia (ALL), seven patients (0·86%) had T‐biphenotypic forms. The clinical and biological characteristics and outcome of these seven patients are reported here. The patients’ median age was 35 years. At diagnosis, all had a tumoural syndrome and five had a mediastinal mass. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Mixed myeloid/T-lymphoid leukemias have been described previously and are thought to represent a variety of diseases with a large genetic heterogeneity, ranging from myeloid leukemias with aberrant expression of only one or few T-cell markers, to "true" biphenotypic leukemias. [34][35][36][37] The T-cell gene most consistently associated with the patient group described here was CD7, which is known to be expressed by a considerable proportion of immature AMLs, [38][39][40] suggesting that the precursor cell in which transformation occurred already had undergone some initial myeloid differentiation. Interestingly, CD7 expression is frequently associated with AMLs carrying CEBPA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed myeloid/T-lymphoid leukemias have been described previously and are thought to represent a variety of diseases with a large genetic heterogeneity, ranging from myeloid leukemias with aberrant expression of only one or few T-cell markers, to "true" biphenotypic leukemias. [34][35][36][37] The T-cell gene most consistently associated with the patient group described here was CD7, which is known to be expressed by a considerable proportion of immature AMLs, [38][39][40] suggesting that the precursor cell in which transformation occurred already had undergone some initial myeloid differentiation. Interestingly, CD7 expression is frequently associated with AMLs carrying CEBPA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were processed according to standard cytogenetic techniques and karyotypes were described according to the International System for Human Cytogenetic Nomenclature (25). ETV6 rearrangements were detected using differentially labeled ETV6 exon-specific cosmids 179A6 (exon 1A), 50F4 (intron 1 and exon 2), 50F4 (exon 2), 163E7 (exons 3-5), 54D5 (exons [5][6][7][8], and 148B6 (exon 8; kindly provided by P. Marynen, Center for Human Genetics, University of Leuven, Leuven, Belgium; ref. 26).…”
Section: Methodsmentioning
confidence: 99%
“…Several reports suggested that patients with MPAL have poor treatment outcomes [1][2][3][4][5]. The low frequency of MPAL in pediatric patients makes it difficult to discover clinical insights of MPAL and the best therapeutic approach for these patients.…”
Section: Introductionmentioning
confidence: 99%